2017
DOI: 10.1097/mib.0000000000001240
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Risk in 2621 Chinese Patients with Inflammatory Bowel Disease

Abstract: In a population-based study, Chinese patients with CD are at an increased risk of anorectal cancers and hematological cancers compared with the general population. A higher risk of nonmelanoma skin cancer was also observed in CD and UC. Cancer surveillance should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 24 publications
3
70
2
Order By: Relevance
“…Among them, six articles focusing on this topic without required data, seven duplicate articles, and 52 articles focusing on other topics were excluded from the meta-analysis. Then, seven articles were included [ 11 , 13 , 19 23 ]. Their references were researched, and no suitable article was found.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, six articles focusing on this topic without required data, seven duplicate articles, and 52 articles focusing on other topics were excluded from the meta-analysis. Then, seven articles were included [ 11 , 13 , 19 23 ]. Their references were researched, and no suitable article was found.…”
Section: Resultsmentioning
confidence: 99%
“…Jung et al and So et al reported that 35.3% and 40.0% of the IBD patients separately in their studies received the immunosuppressant, and these two studies were defined as “ever use” studies [ 13 , 19 ]. Sonu et al in their study and our case-control study reported that the IBD patients did not adopt any kind of immunosuppressant before the development of TC, and these studies were defined as “never use” study [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first description of AML in patients with inflammatory bowel disease was reported in 1980, which identified 5 AML cases among 400 ulcerative colitis patients [2]. In a recent population-based study, using a territory-wide registry in Hong Kong, the risk of acute leukemia was found to be almost 6 times higher in Chinese patients with CD than the general population [3]. With a trend of increasing incidence of inflammatory bowel diseases in Asia [3], it is important to assess complications of disease and to include blood cell counts for surveillance of hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…intestinal flora, diet and infection [1][2][3]. Because the disease is prolonged and prone to recurrent episodes, it increases the risk of colon cancer [4,5]. As one of the important interfaces between the body and the external environment, the intestinal mucosal barrier plays a key role in maintaining intestinal homeostasis.…”
mentioning
confidence: 99%